Penggunaan Wasiat Wajibah bagi Ahli Waris Beda Agama Perspektif Hukum Islam - Marfuah, Fitriyaningsih; Afifah, Nurul; Salamah, Ziadatus (NALAR FIQH: Jurnal Hukum Islam, 2023)
The purpose of this research is to find out about the law on the distribution of inheritance to heirs of different religions in Islam. This study uses library research methods with a case study approach. The focus of this research is in the form of research in the form of the legal concept of fiqh mawaris regarding the division of inheritance. The results of this study indicate that: the law on the distribution of inheritance to heirs of different religions through the intermediary of the obligatory testament is valid based on the decision of the Supreme Court Number 368K/AG/1995 which has been developed from Islamic Compilation Law.